(untitled) (International Journal of Ayurveda and Pharma Research, 2022)
DVT is called as Phlebothrombosis. It is semisolid clot in the vein which has got high tendency to develop pulmonary embolism and sudden death. Most frequent site of thrombosis is calf region. A 60 yr male diagnosed with Deep vein thrombosis (DVT), complaining of pain and swelling on left leg (calf muscle) for 3 months, came in Panchkarma OPD in Chaudhary Brahm Prakash Ayurveda Charak Sansthan New Delhi. Pain and swelling increased with prolonged standing and walking. In Ayurveda Samhitas DVT is not mentioned as separate disease but the symptoms can be correlated with Siraj granthi or Siraja vata. Management: Case was managed according to general guidelines of Sotha, Rakta gata vata and Shiragata dosha. Shaman aushadh and Shaman sneha was given for 3 months. Result: Mild swelling and pain decreased in 15 days of medication. After 2 months, venous Doppler reports suggest partial thrombus noted in external iliac vein, deep femoral vein and popliteal vein shows resolution of thrombus as compared to previous Doppler wells score decreased up to 2